Colecistectomia laparoscópica com três portais em cães viagaslessou pneumoperitônio com CO2 - Linhares, Marcella Teixeira (2021)
The aims of this thesis were, in a first step, to evaluate the results of laparoscopic cholecystectomy (CL) via three-port access in dogs with benign gallbladder diseases in a retrospective study. The second step consisted of proposing and evaluating the feasibility of a gasless three-port access CL in canine cadavers, using a personalized device for mechanical elevation of the abdominal wall, and comparing it to the corresponding technique with pneumoperitoneum in certain surgical variables. In article 1, the medical records of 14 cases of CL performed by two surgeons with different proficiencies were reviewed. The average surgical time was 69.21± 21.7 min (range 45-104), there was no conversion in any of the patients and 85.7% of the dogs were discharged on the day of the procedure. Most intraoperative complications were classified as minor. Two patients had postoperative complications that required reintervention, one of which was unrelated to CL, anddied after the second surgical procedure. In the prospective study of article 2, 16 cadavers were divided into two groups, those from the GCG (n = 8) were submitted to CL using the multidirectional traction platform and those from the GCP (n = 8) underwent CL with pneumoperitoneum (10 mmHg). The total surgical time, the times of each stage of the procedure, and the intraoperative complications were recorded. The degree of difficulty of surgical approaches was assessed by the surgeon and auxiliary fromtwo types of adapted scales, a visual analog scale and a Likert scale. The proposed gasless CL technique was feasible in all animals. The total surgical time was longer for the GCG group (p=0.02), as well as the time for the stage of gallbladder dissection of the liver bed (p=0.03).For both scales, the degree of difficulty in performing the procedure was greater for the GCG in the stages of exposure and dissection of the cystic duct, hemostasis, and transection of the cystic duct, visualization of anatomical structures, and for the sum ofall steps (p<0.05). There was no difference in the incidence of intraoperative complications between the two techniques. Given the results presented, we conclude that CL with three-port access is a viable and safe approach for the treatment of benign gallbladder diseases in dogs, making it possible to reduce the surgical access injury by avoiding the use of an additional trocar, without increasing the complexity of the procedure considering the access of four-port. CL using the multidirectional traction platform was viable in canine cadavers and similar to the corresponding technique using pneumoperitoneum for the incidence of intraoperative complications. Even though the surgical time and the degree of difficulty for the execution of the proposed technique are higher, to enable a CL technique that does not require the use ofpneumoperitoneum represents a valuable alternative for patients unable to compensate for changes caused by abdominal insufflation.